Aspergillosis of Maxillary Sinus in an Uncontrolled Diabetic Patient: A Case Report - Bhavna Barthunia; Arushi Kshetrapal; Yashwant Rao; Shaik M Asif; Kasper D Hundal (Wolters Kluwer Medknow Publications, 2017)
Fungal infections affecting the paranasal sinuses are common. They can affect normal as well as immunocompromised individuals. Aspergillosis and mucormycoses are the most common fungal infections involving maxillary sinus. They can manifest in two forms - noninvasive or invasive infection. These infections when properly diagnosed can be treated at the earliest without causing much tissue damage. Here, a noninvasive form of aspergillosis in an uncontrolled diabetic, elderly female patient is presented. This article also explains the etiopathogenesis, clinical and radiological features, as well as the management of aspergillosis.